PENGARUH GAYA KEPEMIMPINAN DAN KEMAMPUAN MANAJERIAL KEPALA SEKOLAH DASAR TERHADAP KINERJA GURU - Ahmad Muslimin; Rambat Nursasongko (UNIVERSITAS BENGKULU, 2019)
The style or way, and the managerial ability of the principal in his capacity as a leader is crucial to success in improving teacher performance under his / her leadership. The purpose of this research is to obtain data about the influence of leadership style and principal managerial ability on teacher performance. Using a quantitative approach, questionnaire data collection techniques, data analysis techniques with quantitative analysis. The result indicates that leadership style independently gives effect to teacher performance and managerial ability of principal also influences independently of teacher performance, then jointly leadership style and managerial skill of principal have an effect on to teacher performance in primary school at right latitude. It is suggested that the principal can apply a better or varied leadership style and also improve his managerial leadership skills so that the desired goals can be achieved properly and maximally.